Hubungan Pembelajaran Mandiri dengan Minat Belajar Sosiologi Kelas XI IPS di SMAN 1 Gunung Talang Pada Masa Pandemi Covid-19 - Affandi, Achmad; Sylvia, Ike (Naradidik: Journal of Education and Pedagogy, 2022)
This research is a quantitative research with ex post facto type. This is related to the implementation of learning during the Covid-19 pandemic in class XI of SMAN 1 Gunung Talang. The quantitative approach was chosen as the approach because the research focused on how to carry out its activities to achieve the expected goals. The population taken in this study were students who were involved in the implementation of online learning in class XI IPS 1 to IPS 5 in the July-December 2021 semester. The data collection technique used in this study was using a questionnaire. The data analysis technique that researchers will use in this study uses descriptive statistical data analysis methods. The results of this study indicate that there is a relationship between learning independence and interest in learning in class XI IPS SMA 1 Gunung Talang Academic Year 2021/2022 which can be seen from the reliability test of Cronbach's Alpha, the results of the reliability test of the independent variable in learning obtained a reliability value of 0.713 then reliability the measuring tool is good, while for the learning interest variable the reliability value is 0.705, the reliability is good. Both variables have good reliability, meaning that these items are very reliable as a data collection tool in this study.